2021
DOI: 10.20945/2359-3997000000320
|View full text |Cite
|
Sign up to set email alerts
|

Is there a place for measuring serum calcitonin prior to thyroidectomy in patients with a non-diagnostic thyroid nodule biopsy?

Abstract: Objective: To verify the cytopathological Bethesda System classification of thyroid nodule fine-needle aspiration biopsy (FNAB) in MTC patients and to assess the role of preoperative serum calcitonin (CT) levels in the investigation of this neoplasm in medullary thyroid cancer (MTC) patients under observation at the Uopeccan (União Oeste Paranaense de Estudos e Combate ao Câncer). Materials and methods: This is a cross-sectional review of medical records of patients monitored at the thyroid cancer outpatient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Calcitonin measurement helped diagnosis in 1 of 427 cases with AUS/FLUS cytology, and indicated MTC in 2 of 73 cases with FN/SFN cytology. An indeterminate cytology result was found at the rate of 0-30% in the previous studies investigating the FNAB results of large medullary cancer case series, which was similar to the current case series [ 4 , 18 , 33 ]. While routine calcitonin measurement seems to be reasonable in cases with FN/SFN, in cases with multiple AUS cytology, instead of routine calcitonin measurement, calcitonin can be screened particularly in patients with suspicious features of MTC on ultrasonography or with a family history of MTC [ 6 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Calcitonin measurement helped diagnosis in 1 of 427 cases with AUS/FLUS cytology, and indicated MTC in 2 of 73 cases with FN/SFN cytology. An indeterminate cytology result was found at the rate of 0-30% in the previous studies investigating the FNAB results of large medullary cancer case series, which was similar to the current case series [ 4 , 18 , 33 ]. While routine calcitonin measurement seems to be reasonable in cases with FN/SFN, in cases with multiple AUS cytology, instead of routine calcitonin measurement, calcitonin can be screened particularly in patients with suspicious features of MTC on ultrasonography or with a family history of MTC [ 6 ].…”
Section: Discussionsupporting
confidence: 90%
“…Measurement of serum calcitonin is a sensitive and specific marker in the diagnosis and follow-up of MTC [ 13 , 15 ] and it is well known that the most important factor in MTC prognosis is early diagnosis of the disease [ 13 , 16 ]. Calcitonin measurement has been shown to be superior to FNAB in MTC detection in the previous studies [ 4 , 17 , 18 ] Nevertheless, routine calcitonin measurement in nodular thyroid disease is controversial. Although the detection of MTC through routine calcitonin screening has recently been shown to lead to early stage diagnosis, the ATA guideline did not make recommendations for routine calcitonin measurement in nodular thyroid patients, leaving the decision up to the clinicians [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 25 articles 19–43 found according to the criteria of the present systematic review were published between 2002 and 2021. The authors were from eastern countries in 18 papers, European in five, and American in two.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 25 studies could be included in the systematic review (Figure 1 ). 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 …”
Section: Resultsmentioning
confidence: 99%
“…Del Rio, Rico, Bordiu, & Novoa, 1987). Oliveira et al,( 2021) detected a reduction in calcitonin levels after thyroidectomy (Oliveira et al, 2021). Qu et al, (2022), (Tinawi, 2021) andCornelius, (2020) suggested that hypoalbuminemia may be the main factor in the pathogenesis of postoperative hypocalcemia, when only total calcium is measured.…”
Section: Calcitoninmentioning
confidence: 99%